The effect of the Ayas model to learning individual fast attack and high-order thinking skills of handball for students - Hussein, Ali Radhi Abdul (Universitas Tanjungpura, 2025)
Background and Study Aim. The significance of this research lies in designing a specialized scale to evaluate advanced cognitive skills related to handball among students. It also examines the impact of the Ayas model on enhancing these higher-order thinking skills and teaching the technique of the individual fast attack in handball. This study aimed to investigate the effect of the Ayas Model on learning individual fast attack techniques and higher-order thinking skills in handball among students.Material and Methods. The experimental method was adopted, involving a sample of 64 third-year students from the College of Physical Education and Sports Sciences at the University of Babylon. The sample was divided into two groups: an experimental group (32 students), taught using the Ayas Model, and a control group (32 students), taught using traditional methods. Pre- and post-tests were conducted to assess the students